Restriction of multiple divergent retroviruses by Lv1 and Ref1 - Hatziioannou, Theodora; Cowan, Simone; Goff, Stephen P.; Bieniasz, Paul D.; Towers, Greg J. (The EMBO journal, 2003)
The mouse gene Fv1 encodes a saturable restriction factor that selectively blocks infection by N‐tropic or B‐tropic murine leukemia virus (MLV) strains. Despite the absence of an Fv1 gene, a similar activity is present in humans that blocks N‐MLV infection (Ref1). Moreover, some non‐human primate cell lines express a potentially related inhibitor of HIV‐1 and/or SIVmac infection (Lv1). Here, we examine the spectrum of retrovirus‐restricting activities expressed by human and African green monkey cell lines. Human cells restrict N‐MLV and equine infectious anemia virus (EIAV), but not HIV‐1, HIV‐2, SIVmac or SIVagm, whilst AGM cells restrict N‐MLV, EIAV, HIV‐1, HIV‐2 and SIVmac. Remarkably, in each example examined, restriction of infection by a given retrovirus can be abrogated at least partially by saturation with another retrovirus, provided that it is also restricted but regardless of whether it is closely related. These data suggest that restriction factors in human and non‐human primate cells are able to recognize and block infection by multiple, widely divergent retroviruses and that the factors themselves may be related.